Novel oral anticoagulants and trauma: The results of a prospective American Association for the Surgery of Trauma Multi-Institutional Trial. Issue 5 (May 2017) - Kobayashi, Leslie; Barmparas, Galinos; Bosarge, Patrick; Brown, Carlos V.; Bukur, Marko; Carrick, Matthew M.; Catalano, Richard D.; Holly-Nicolas, Jan; Inaba, Kenji; Kaminski, Stephen; Klein, Amanda L.; Kopelman, Tammy; et al.
Abstract : BACKGROUND: The number of anticoagulated trauma patients is increasing. Trauma patients on warfarin have been found to have poor outcomes, particularly after intracranial hemorrhage (ICH). However, the effect of novel oral anticoagulants (NOAs) on trauma outcomes is unknown. We hypothesized that patients on NOAs would have higher rates of ICH, ICH progression, and death compared with patients on traditional anticoagulant and antiplatelet agents. METHODS: This was a prospective observational trial across 16 trauma centers. Inclusion criteria was any trauma patient admitted on aspirin, clopidogrel, warfarin, dabigatran, rivaroxaban, or apixaban. Demographic data, admission vital signs, mechanism of injury, injury severity scores, laboratory values, and interventions were collected. Outcomes included ICH, progression of ICH, and death. RESULTS: A total of 1, 847 patients were enrolled between July 2013 and June 2015. Mean age was 74.9 years (SD ± 13.8), 46% were female, 77% were non-Hispanic white. At least one comorbidity was reported in 94% of patients. Blunt trauma accounted for 99% of patients, and the median Injury Severity Score was 9 (interquartile range, 4–14). 50% of patients were on antiplatelet agents, 33% on warfarin, 10% on NOAs, and 7% on combination therapy or subcutaneous agents. Patients taking NOAs were not at higher risk for ICH on univariate (24% vs. 31%) or multivariate analysis (incidence rate ratio, 0.78; confidence interval 0.61–1.01, p = 0.05). Compared with all other agents, patients on aspirin (90%, 81 mg; 10%, 325 mg) had the highest rate (35%) and risk (incidence rate ratio, 1.27; confidence interval, 1.13–1.43; p < 0.001) of ICH. Progression of ICH occurred in 17% of patients and was not different between medication groups. Study mortality was 7% and was not significantly different between groups on univariate or multivariate analysis. CONCLUSION: Patients on NOAs were not at higher risk for ICH, ICH progression, or death. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III. Abstract : Supplemental digital content is available in the text.